Performance Evaluation of Maoming Science and Technology Finance based on Malmquist-DEA model - Wu, Ganzhou (International Journal of Global Economics and Management, 2024)
Since the Malmquist index can analyze the change of decision-making units at different times and eliminate the factors of technological progress, it can get more accurate results than cross-sectional data. Therefore, by introducing Malmquist index and combining with BCC-DEA model, this paper analyzes the efficiency of the combination of science, technology and finance in different periods in Guangdong province, this provides a strong theoretical support for Maoming’s co-ordination of science and Technology Innovation and Technology Finance. The study found that Maoming’s innovation output was at the average level of Guangdong, but compared with Zhuhai and Shenzhen, Science and technology innovation was less dynamic and was at an unbalanced stage of development.